2006
DOI: 10.1093/wber/lhj007
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure, Externalities, and Economic Development: A Study of the Indian Manufacturing Industry

Abstract: If infrastructure tends to generate spillover externalities, as has been the assumption in much of the development literature, one may reasonably look for evidence of such indirect effects in the accounts of manufacturing industries. Empirical support for this assumption has so far been ambiguous. This analysis of Indian data, however, reveals substantial externality effects from the states' infrastructure to manufacturing productivity. The analysis separates the direct effects of roads and electricity, as med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
100
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(128 citation statements)
references
References 23 publications
6
100
0
5
Order By: Relevance
“…To appropriately map the sectors in our data onyo the ones in the input-output matrix we had to group our initial set of 16 manufacturing sectors into 12 which left us with a total of 17 sectors. 10 The equation we estimate is as follows: Variation in skill intensity across sectors is captured by Skill_Int which equals the total remunerations of the highly skilled as a percentage of the total remunerations of all the workers (skilled plus unskilled). These skill intensities are reported in Table 7.…”
Section: Disaggregated Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To appropriately map the sectors in our data onyo the ones in the input-output matrix we had to group our initial set of 16 manufacturing sectors into 12 which left us with a total of 17 sectors. 10 The equation we estimate is as follows: Variation in skill intensity across sectors is captured by Skill_Int which equals the total remunerations of the highly skilled as a percentage of the total remunerations of all the workers (skilled plus unskilled). These skill intensities are reported in Table 7.…”
Section: Disaggregated Resultsmentioning
confidence: 99%
“…The intensity ratios for roads (Road_Int) and power (Power_Int) are defined as the 10 The exact mapping is stated in Table 6.…”
Section: Disaggregated Resultsmentioning
confidence: 99%
“…Assume, as in Hulten et al (2005) that infrastructure (denoted X in the following equations) influences output through two channels. First, it impacts TFP through…”
Section: Growth Accounting With Infrastructurementioning
confidence: 99%
“…For instance, Hulten, Bennathan, and Srinivasan (2006) found that in India, from 1972 to 1992, highways and electricity accounted for almost half of the growth of the Solow residuals of the manufacturing industries. The positive productivity effects of physical infrastructure development can be found even in rural areas and agricultural sectors (Jimenez, 1995;Fan and Zhang, 2004;and Zhang and Fan, 2004).…”
Section: Introductionmentioning
confidence: 99%